Echocardiographic Assessment of Systolic Myocardial Dysfunction in Children with Chronic Kidney Disease - Mamun, Abdullah Al; Rahman, Md. Habibur; Jesmin, Tahmina; Huque, Saimul; Begum, Afroza; Uddin, Golam Muin; Roy, Ranjit Ranjan (Journal of Pediatric Nephrology, 2020)
Background and Aim: Chronic Kidney Disease (CKD) is associated with significantly increased morbidity and mortality. Cardiovascular causes contribute to the large proportion of morbidity and mortality in this group. The aim of the current study was to assess systolic myocardial dysfunction of the heart in children with chronic kidney disease (stage V). Methods: This cross-sectional study was carried out in a tertiary center from January 2018 to December 2018. Children aged 1 to 18 years having chronic kidney disease (stage V) were included in the study. All the patients underwent color Doppler echocardiography for the evaluation of cardiac abnormalities. Age and sex-matched healthy children with no clinical evidence of renal and cardiovascular disease were taken as a comparison group. Results: Out of Thirty children with Chronic kidney disease (stage V), 21(70%) were male and 9 (30%) female. Echocardiographic findings revealed a statistically significant difference in case of CKD patients group and a comparison group in relation with left atrium (LA), left ventricular internal diameter in diastole (LVIDd), left ventricular internal diameter in systole (LVIDs), interventricular septum in diastole (IVSd), interventricular septum in systole (IVSs), left ventricular posterior wall thickness in diastole (LVPWd) and left ventricular posterior wall thickness in systole (LVPWs) (p<0.001) but no difference in relation to FS and EF (p-0.934 & p-0.754 respectively). Conclusion: It can be concluded from the present study that children with chronic kidney disease are prone to develop left ventricular structural abnormality but systolic functional changes are less frequent.